The Contribution of Karang Taruna Merdeka Jaya in Growing Social Concern of the Young Generation in Wora Village - Arfaton; Gilar Wullida Ayuningtiyas; Khofifah Nur Rahmah; Griselda Afni Wulandari; Ni Luh Wika Kristina; Novi Herawati (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze the contribution of Karang Taruna Merdeka Jaya in fostering social awareness among the younger generation. The research method uses qualitative descriptive data collection, which is carried out through interviews, observation, and documentation. Data analysis is carried out in four stages: data collection, data reduction, data presentation, and verification. The results of this study indicate that Karang Taruna Merdeka Jaya plays an active role in fostering social awareness among the younger generation. The contribution of Karang Taruna Merdeka Jaya in fostering social awareness among the younger generation can be seen from its various work programs, such as Bakti Sosial Merdeka, Sanggar Seni Merdeka Jaya, Annual Tournament, Muda Mengaji Merdeka, Edukasi dan Literasi Merdeka, and Gerakan Merdeka Hijau. The younger generation's involvement in Karang Taruna Merdeka Jaya activities impacts increasing attitudes of empathy and solidarity, attitudes of social responsibility, and positive changes in attitudes. Research is expected to contribute to youth organizations forming positive characters for the younger generation in the future.